Resisting the Algorithmic Management of Science: Craft and Community After Generative AI - Bechky, Beth A.; Davis, Gerald F. (Administrative Science Quarterly, 2025)
This essay in honor of ASQ's 70th volume surveys how technology-driven changes in scholarly publishing have introduced algorithmic management to organizational research. The internet greatly reduced the cost of publishing journals and prompted an orders-of-magnitude increase in the number of journals and articles while also foregrounding quantitative metrics for scholarship. Given the academic incentive system of publish or perish, the new online ecosystem has encouraged problematic practices by scholars and publishers that threaten the standards and values of organizational theory. The advent of generative artificial intelligence within this milieu is almost certain to worsen the publishing trends we have already experienced. Drawing on prior literature about the centrality of deep intellectual engagement through reading, writing, and interactions with colleagues, we propose a set of reforms to preserve the sacredness of craft and community at the core of our scholarly work.